VARUMÄRKETS KORTSLUTNING? - “STOCKHOLM THE CAPITAL OF SCANDINAVIA” - Franzén, Mats (K&K - Kultur og Klasse, 2010)
THE SHORT-CIRCUITING OF A BRAND? - “STOCKHOLM – THE CAPITAL OF SCANDINAVIA” Ever since 2005 Stockholm has been promoted by a new brand: “Stockholm – the Capital of Scandinavia”. However, the question is whether a brand saying only that Stockholm is the number one city in Scandinavia really works. Before giving an answer to this question, the phenomenon of city branding is discussed in more general terms. This makes it possible to identify three ways in which the successful promotion of Stockholm might be short-circuited. First, since the use of this brand is open to anyone who wants to use it and the trademark has not been registered, any control over its use is lost (yet abuse is highly unlikely). Second, and more problematically, this brand does not resonate with the intrinsic logic of Stockholm, which means that it will not be used by the city’s own inhabitants. Third, the planned promotion of the city by the brand is directed mainly (and too instrumentally) at an international business elite, which underlines the risk of the second short-circuiting possibility as well as risking the social cohesion of the city. However problematic this new brand is, economically speaking Stockholm has prospered in recent decades – so perhaps the brand is simply unnecessary.